Asmat Indigenous Participation in Development through Participatory Mapping: : A Political-Anthropological Reflection - Hada, Hendrikus; Poli , Agustina Ivonne (Universitas Andalas, 2025)
This study describes the process of participation of the indigenous people of the Asmat group of Pomar Sirau in participatory mapping and analyzes their participation rate based on the Arnstein Degree of Participation. Using a qualitative approach with a case study method, data was collected through in-depth interviews, participatory observations, Focus Group Discussions (FGDs), and document studies. The results of the study show that community participation takes place through several stages, starting from community awareness of threats to customary lands, community initiatives in voicing problems, to active involvement in mapping customary territories. Based on the Arnstein Degree of Participation, community participation is at the level of